Femoral and Tibial Tunnel Positioning on Graft Isometry in Anterior Cruciate Ligament Reconstruction: A Cadaveric Study. (December 2014) - Smith, James O; Yasen, Sam; Risebury, Mike J; Wilson, Adrian J
Purpose: To assess distance changes between the femoral and tibial attachment points of 3 different anterior cruciate ligament (ACL) tunnel entry positions throughout the range of knee motion in cadaveric knees. Methods: The ACLs of 11 fresh-frozen cadaveric knees (from 6 men and 5 women) were removed using radiofrequency. Three tibial tunnel placements were made using a cannulated awl, and three 2.4-mm pilot tunnels were drilled on the lateral femoral condyle. One end of an inelastic suture was inserted from each of the 3 femoral holes and fixed on the femoral cortex using a suture button in turn, whereas the other end of the suture was passed through the cannulated awl and fixed on each of the 3 tibial placements in turn, with constant tension. Distance changes of the suture throughout the range of knee movement (0°, 90°, and 135° of knee flexion) were measured for each combination of tibial and femoral positions. Results: The distance was minimum when the knee was in full extension (p±0.0001). Most of the distance changes occurred during initial flexion (0°–90°). The most isometric position (mean±standard deviation [SD] distance change, 2.78±0.93 mm; p±0.0001) was noted when the suture was at the anteromedial bundle placement in the femur and anterior in the tibia. The least isometric position (mean±SD distance change, 10.37±2.08 mm; p±0.0001) was noted when the suture was at the mid-bundle position in the femur and at the posterolateral bundle insertion in the tibia. The anatomic position resulted in a mean±SD distance change of 7.63±2.01 mm (p±0.0001). The femoral position had a greater influence on distance change than the tibial position. Conclusion: None of the ACL graft positions was isometric. Anatomic ACL positioning resulted in comparable anisometry to the native ACL. The minimum distance for all graft positions was noted in full extension, in which position the graft should be fixed during anatomic ACL reconstruction.